Strategic human resource management and organizational performance: a case study from an Egyptian nonprofit organization - Abdelmeguid, Nivin (AUC Knowledge Fountain, 2014)
This study examines the relationship between strategic human resource management (SHRM) and organizational performance outcomes in Egyptian nonprofit organizations. The study uses a mixed-methods approach where quantitative research is followed by in-depth interviews to test the proposed relationships among variables at a growing human services nonprofit organization operating in Cairo. Data helped in identifying relationships between four unique SHRM configurations (retention, acquisition, training and internal labor market) and two workforce characteristics (employee intent to leave and human capital) proven by empirical literature to have a direct impact on perceptual measures of organizational performance. While research results suggested that measures of turnover were found to directly improve organization-level performance, data did not assert that measures for human capital (work experience and education level) directly enhance performance. However, these measures were found to be positively associated with acquisition and training in the context of human resource (HR) practices.